The influence of hydrogen on the resistance to the formation of cracks in welded joints of water supply pipelines - Makarenko, V.; Gots, V.; Berdnyk, O.; Amelina, N.; Yasenova, I. (Ways to Improve Construction Efficiency, 2023)
The existing scientific and practical studies of the influence of hydrogen on the parameters of crack resistance are characterized by uncertainty and contradiction, the lack of clear ideas about the mechanism of the initiation and propagation of cold cracks, and therefore there are no balanced approaches to combating the formation of cracks during the long-term operation of pipelines, and therefore additional studies are needed. It was established that with an increase in the content of diffusible hydrogen in the deposited metal, the resistance to its brittle destruction decreases sharply. Thus, with a hydrogen content of 8,1 cm3/100g in the deposited metal and a cooling rate Wohl = 4,0 0С/s, the crack initiation work Azt = 1,5 J, and at 1,5 cm3/100g, the value of Azt increases to 17,6 J, that is, more than 11 times. When the hydrogen content is higher than 5,0 cm3/100g, and Wohl = 55 0C/s, the Azt value is practically zero. It is shown that with an increase in the hydrogen content in the weld, the work of crack propagation also decreases Art. Thus, with a hydrogen concentration of 1,0 cm3/100g for a welded joint on steels 09Г2С and 17Г1С at Wohl = 4.0 0С/100g, the value of Art = 48,5 J/cm2, and when its content increases to 8,0 cm3/100g, the work of Art decreases to 18,5 J /cm2, i.e. approximately 2,7 times. A decrease in the air temperature during welding to -30...-40 0С and an increase in the concentration of dissolved hydrogen in the weld seam to 5–8 cm3/100g lead to an increase in the critical brittleness temperature by approximately 40–500С. Plastic deformations that inevitably occur in welded joints and structures, according to their nature of occurrence in the process of the technological cycle of manufacturing and operation of a welded structure, can be divided into the following groups: a) initial deformations in the base metal, which depend on the method of obtaining and processing the metal, foundry, powder metallurgy, pressure (rolling, stamping, forging); b) deformations occurring during procurement operations and assembly, cutting, straightening, bending, rolling, fixing on assembly devices; c) welding deformations arising as a result of the thermal deformation cycle of welding; d) technological deformations; d) operational deformations that may occur during operation as a result of local overloads, loss of stability, etc.